2008
DOI: 10.2478/s11534-008-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Onset of local ordering in some copper-based alloys: critical solute concentration vis-a-vis various solutionhardening parameters

Abstract: Abstract:The mode of planar distribution of solute atoms in Cu single crystals alloyed with 0.5 to 8.0 at.%Ge has been investigated via the temperature dependence of the critical resolved shear stress of these alloys. It is found that there exists a critical solute concentration ≈ 5 at.%Ge below which the distribution of solute atoms in the crystal is random, and above which some local ordering occurs. This together with such data available in the literature for Cu-Zn, Cu-Al and Cu-Mn alloys, i.e.≈ 27 at. %Zn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Since the mechanical response of alloys is sensitive to the nature of solute distribution [19][20][21][22], dispersion of second-phase particles [23][24][25], etc., we shall now critically examine the published data on the strength of thermally-activable barrier, U o , which determines the stress-relaxation rate, s , in polycrystalline copper and ␣-brasses together with that obtained for Cu-42.2 at.%Zn-0.6 at.%Pb alloy in the present investigations. appertaining to 99.999 at.% pure copper and ␣-brass polycrystals containing nominally 12, 20, 30 and 35 at.% Zn, deformed by Ghauri [5] at room temperature, whereas the U o -value for 42.2 at.%Zn belongs to the present work.…”
Section: Stress-relaxation Versus Alloy Microstructurementioning
confidence: 99%
“…Since the mechanical response of alloys is sensitive to the nature of solute distribution [19][20][21][22], dispersion of second-phase particles [23][24][25], etc., we shall now critically examine the published data on the strength of thermally-activable barrier, U o , which determines the stress-relaxation rate, s , in polycrystalline copper and ␣-brasses together with that obtained for Cu-42.2 at.%Zn-0.6 at.%Pb alloy in the present investigations. appertaining to 99.999 at.% pure copper and ␣-brass polycrystals containing nominally 12, 20, 30 and 35 at.% Zn, deformed by Ghauri [5] at room temperature, whereas the U o -value for 42.2 at.%Zn belongs to the present work.…”
Section: Stress-relaxation Versus Alloy Microstructurementioning
confidence: 99%
“…So is the case for other mechanical properties of solid-solution crystals, such as workhardening rate [22], internal friction [23], creep [22,24], stress relaxation [25,26], and strain rate sensitivity of flow stress [27]. To explore the relationship between the temperature dependence of critical resolved shear stress (CRSS) of solid-solution crystals and the nature of solute distribution, Butt and co-workers [13][14][15][16] carried out investigations with a number of copper-based binary alloy systems. They found that the CRSS of Cu-Zn [13], Cu-Al [14], Cu-Ge [15] and Cu-Mn [16] varies with the deformation temperature T in accord with the relation:…”
Section: Introductionmentioning
confidence: 99%
“…To explore the relationship between the temperature dependence of critical resolved shear stress (CRSS) of solid-solution crystals and the nature of solute distribution, Butt and co-workers [13][14][15][16] carried out investigations with a number of copper-based binary alloy systems. They found that the CRSS of Cu-Zn [13], Cu-Al [14], Cu-Ge [15] and Cu-Mn [16] varies with the deformation temperature T in accord with the relation:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation